Wood‐Derived Materials for Advanced Electrochemical Energy Storage Devices. (6th June 2019) - Huang, Jianlin; Zhao, Bote; Liu, Ting; Mou, Jirong; Jiang, Zhongjie; Liu, Jiang; Li, Hexing; Liu, Meilin
Abstract: Over the past decade, wood‐derived materials have attracted enormous interest for both fundamental research and practical applications in various functional devices. In addition to being renewable, environmentally benign, naturally abundant, and biodegradable, wood‐derived materials have several unique advantages, including hierarchically porous structures, excellent mechanical flexibility and integrity, and tunable multifunctionality, making them ideally suited for efficient energy storage and conversion. In this article, the latest advances in the development of wood‐derived materials are discussed for electrochemical energy storage systems and devices (e.g., supercapacitors and rechargeable batteries), highlighting their micro/nanostructures, strategies for tailoring the structures and morphologies, as well as their impact on electrochemical performance (energy and power density and long‐term durability). Furthermore, the scientific and technical challenges, together with new directions of future research in this exciting field, are also outlined for electrochemical energy storage applications. Abstract : Recent progress in the development of wood and its derivative materials for advanced energy storage devices, including supercapacitors and rechargeable batteries, is reviewed, in particular for their micro/nanostructure, structure engineering strategies, and electrochemical performance.